Analisis Pemikiran Raden Ajeng Kartini Perspektif Sosio-Religi (1889-1904 M) - Rizkillah, Ammar (TARIKHUNA: JURNAL SEJARAH PERADABAN ISLAM, 2025)
Abstract Raden Ajeng Kartini, commonly known as R.A. Kartini, was a prominent figure whose visionary thinking set her apart as a pioneer in advocating for women's rights and intellectual freedom. Her progressive views are reflected in both her tangible actions and her written expressions, which have been widely studied and analyzed. One of the core themes she frequently addressed was the socio-religious dimension, which forms the primary focus of this paper. This study seeks to explore the socio-religious discourse of the 19th century through an analytical examination of Kartini's thoughts, based on various available sources. The research utilizes data derived from books, academic journals, and other relevant scientific literature, encompassing both primary and secondary sources. Among the primary sources employed are Letters of a Javanese Princess and Habis Gelap Terbitlah Terang by Empat Saudara. A qualitative method is employed in this study, presented in a narrative-descriptive format. The researcher conveys the chronological development of the subject matter and provides an in-depth analysis of the events and ideas discussed. From a methodological perspective, this study is categorized as historical research using a synchronic approach—analyzing historical events from multiple dimensions and perspectives. Data collection is conducted through library research, allowing for a comprehensive review of relevant literature. Keywords: Kartini, Thought, Socio-Religious, 19th Century